On-Line Fault Diagnostics Of Three Phase Squirrel Cage Induction Motor Based On Motor Current Signature Analysis Method - Hammadi, Khaleel J. (2012)
Studies of rotor asymmetries in three-phase squirrel cage induction motors have traditionally focused on analyses of the effects of the broken rotor bars on the magnetic field and current spectrum. Major motor manufactures have reported cases where damage bars are randomly distributed around the rotor perimeter of large motors. The motors were being monitored under maintenance programs based on motor current signature analysis (MCSA) in some of these cases, and the degree of degradation found in the rotor was much greater than that predicted by analysis of their current spectra. A complete study was carried out for this reason, comprising a theoretical analysis, as well as simulation and test, to investigate the influence that the number and location of broken bars has on the traditional MCSA diagnosis procedure.